Maternal Lifestyle Factors and Fetal Macrosomia Risk: A Review - Kathy M. Redfern; Gail A. Rees; Jonathan H. Pinkney (European Medical Journal, 2016)
Fetal macrosomia is associated with a number of health complications for both mother and infant in the immediate, short, and long-term. Maternal obesity and excessive gestational weight gain (GWG) have long been associated with fetal macrosomia, however the impact of maternal lifestyle factors such as dietary intake and energy balance, in combination with the timing and composition of weight gain, have been less studied. It is also clear that although maternal obesity and excessive GWG increase the risk of fetal macrosomia independently, the risk is magnified with the presence of both risk factors, suggesting that interventions to control GWG may be particularly important for obese women. Association studies examining the relationship between fetal nutrient availability, epigenetic modifications, and infant anthropometrics are also required. This review provides an overview of the current evidence examining the role of maternal lifestyle factors on the prevalence of fetal macrosomia and identifies areas where further research is required in order to inform the design of appropriate intervention strategies.